Restrictions on the parameters of the Minimal Supersymmetric Standard Model with CP-violation - Gurskaya Albina; Dolgopolov Mikhail; Rykova Elza (EPJ Web of Conferences, 2019)
The minimal supersymmetric extension of the standard model with CP-violation is considered in this paper. The main area of the model parameters, which is attractive for researchers, corresponds to small values of the tangent mixing angle of two doublets Higgs fields (tanβ). The authors discuss the possibilities of the model in correlation with the data on the search for the lightest stable supersymmetric particle. The masses of neutral Higgs bosons in the basis of CP-violationwas calculated.The results are presented as dependencies neutral CP-odd Higgs boson mass mA on tanβ. At small values tgβ the mass of the lightest stable particle must be more than ∼ 250 GeV.